Kecenderungan Perilaku Cyerbullying Ditinjau dari Traits dalam Pendekatan Bigfive Personality pada Siswa Sekolah Menengah Atas Negeri di Kota Yogyakarta - Ageng Larasati; Maya Fitria (Jurnal Psikologi Integratif, 2016)
The aim of this research was to understand the relationship between the bigfive personality traits with tendency of cyberbullying behavior. This research was conducted in the state senior highschool students Yogyakarta, in which 81 students respondents. The research use work the tendency of cyberbullying behavior measurement consisted of 46 items and the bigfive personality traits measurement consisted of 18 items. The data which obtained through work tendency of cyberbullying scale, and the bigfive personality traits scale were analyzed statistic method with regression analysis. Result of analyzed data obtained correlation coefficient R = 0.575 with p = 0.000 (p<0.05). As it showed that there was significant correlation between the bigfive personality traits and the tendency of cyberbullying behavior. Traits of personality which had significant correlation with the tendency of cyberbullying behavior were agreeableness obtained correlation coefficient R = -0.331 with p = 0.010 (p<0.05), and conscientiousness obtained correlation coefficient R = 0.315 with p = 0.004 (p<0.05). Were as other traits of personality which were extraversion, neuroticism, and openness had not indicated the correlation with tendency of cyberbullying behavior.